2013
DOI: 10.1186/1752-0509-7-94
|View full text |Cite
|
Sign up to set email alerts
|

Noise propagation through extracellular signaling leads to fluctuations in gene expression

Abstract: BackgroundCell-to-cell variability in mRNA and proteins has been observed in many biological systems, including the human innate immune response to viral infection. Most of these studies have focused on variability that arises from (a) intrinsic stochastic fluctuations in gene expression and (b) extrinsic sources (e.g. fluctuations in transcription factors). The main focus of our study is the effect of extracellular signaling on enhancing intrinsic stochastic fluctuations. As a new source of noise, the communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 48 publications
(75 reference statements)
0
18
0
Order By: Relevance
“…When infected by viruses, individual cells variably respond in an ''all-or-none'' fashion to activate the IFNB1 gene due, at least in part, to the stochastic assembly of the IFNB1 enhanceosome in a fraction of infected cells only (Hu et al, 2007;Apostolou and Thanos, 2008;Tabbaa et al, 2013;Zhao et al, 2012). In addition, positive and negative feedback loops manifested by the autocrine and paracrine action of the secreted IFNB1 protein further contribute to the stochastic IFNB1 gene expression (Rand et al, 2012;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When infected by viruses, individual cells variably respond in an ''all-or-none'' fashion to activate the IFNB1 gene due, at least in part, to the stochastic assembly of the IFNB1 enhanceosome in a fraction of infected cells only (Hu et al, 2007;Apostolou and Thanos, 2008;Tabbaa et al, 2013;Zhao et al, 2012). In addition, positive and negative feedback loops manifested by the autocrine and paracrine action of the secreted IFNB1 protein further contribute to the stochastic IFNB1 gene expression (Rand et al, 2012;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions, which are stochastic in nature, occur only in the fraction of the cell population that expresses the IFNB1 gene and involve one IFNB1 allele and one allele of a single NRC. Enhancer-bound NF-kB nucleates the assembly of the IFNB1 enhanceosome causing early mono-allelic IFNB1 gene expression (Apostolou and Thanos, 2008;Tabbaa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was initially observed in the stochastic inactivation of one X chromosome in the somatic cells of female mammals (Lyon, 1961). In autosomal genes, the inactivation of one allele was observed firstly in olfactory receptors (Chess et al, 1994) and cytokine genes IL-2 (Holländer et al, 1998), IL-4 (Rivière et al, 1998) and IFNB1 (Tabbaa et al, 2013), among others. The mechanism of DNA looping, in the form of interchromosomal interactions, has also been shown to play a role in the regulation of stochastic monoallelic expression of the olfactory receptor genes in neurons (Lomvardas et al, 2006) and in response to viral infection for the IFNB1 gene (Apostolou and Thanos, 2008).…”
Section: Sources Of Transcriptional Variabilitymentioning
confidence: 99%
“…To study the full innate immune response, we infected DCs with NDV, a virus that lacks effective immune antagonists for human cells. Multiscale agent-based modeling has shown that the single-cell variation in the secretion of IFN is predicted to generate a spatially heterogeneous response of IFN-inducible genes (46). The propagation of noise within one cell type and in complex organs, such as the lung, is an important area for investigation.…”
Section: Paracrine Signaling Implicated In Temporal Dispersion Of Sinmentioning
confidence: 99%